2012
DOI: 10.1093/humrep/des064
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the prostate and testis expression (PATE)-like proteins in sperm-oocyte interaction

Abstract: background:The prostate and testis expression (PATE)-like family of proteins are expressed mainly in the male genital tract. They are localized in the sperm head and are homologous to SP-10, the acrosomal vesicle protein also named ACRV1. Our aim was to characterize the expression and functional role of three PATE-like proteins in the testis and ejaculated sperm. methods:The expression and localization of PATE-like proteins in human testis biopsies (n ¼ 95) and sperm cells were assessed by RT-PCR, immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Incubation of mouse spermatozoa with polyclonal antibody specific to PATE inhibited sperm-oolemma fusion and not sperm-zona binding (Margalit et al, 2012). Similarly, SP-10, a protein similar to PATE was found to play a role in sperm-egg binding and oolemma penetration (Hamatani et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Incubation of mouse spermatozoa with polyclonal antibody specific to PATE inhibited sperm-oolemma fusion and not sperm-zona binding (Margalit et al, 2012). Similarly, SP-10, a protein similar to PATE was found to play a role in sperm-egg binding and oolemma penetration (Hamatani et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Although the human PATE proteins were found to be involved in sperm-oolemma fusion and penetration, but not in sperm-zona binding (Margalit et al, 2012), their role in sperm maturation and capacitation are not yet reported. Because of their segment-specific expression in the epididymis, differential localization on the sperm and difference in their functional roles, it is possible that they may also play varied roles in sperm function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their three-dimensional structures indicate that they are similar to the three-fingered proteins (Ploug & Ellis, 1994;Fry et al, 2003), uPAR and murine Ly-6 GPI-anchored proteins (Ploug & Ellis, 1994), and activin receptors (Ploug, 2003). PATE proteins are abundantly expressed in the male reproductive tract and on the spermatozoa (Soler-Garcia et al, 2005;Levitin et al, 2008;Turunen et al, 2011;Margalit et al, 2012). We also demonstrated their expression pattern in the male reproductive tract of rat and the dynamics of expression during sperm capacitation and acrosome reaction, besides their role in fecundity (Rajesh & Yenugu, 2012, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…PATE proteins conserve two characteristic motifs that contain 10 cysteine residues: C [XX]C[X7-8]C[X6]C[X7-8]C and C[X3]C[X15-16]CC[X4-5]CN; with a dipeptide sequence (cysteine-asparagine) at the C-terminal formed with the 10th cysteine of the second motif (Bera et al, 2002). PATE proteins are abundantly expressed in the male reproductive tract and on the spermatozoa (Soler-Garcia et al, 2005;Levitin et al, 2008;Turunen et al, 2011;Margalit et al, 2012). PATE proteins are abundantly expressed in the male reproductive tract and on the spermatozoa (Soler-Garcia et al, 2005;Levitin et al, 2008;Turunen et al, 2011;Margalit et al, 2012).…”
Section: Introductionmentioning
confidence: 99%